Prehypertension status, cardiometabolic risks, and decreased baroreflex sensitivity are linked to sympathovagal imbalance in salt-preferring individuals. (17th November 2015) - Pal, Gopal Krushna; Chandrasekaran, Adithan; Pal, Pravati; Nivedita, Nanda; Indumathy, Jagadeeswaran; Sirisha, Allampalli
Abstract: Salt preference has been reported to cause sympathovagal imbalance (SVI) and prehypertension. We investigated the role of inflammation, insulin resistance (IR), hyperlipidemia, and oxidative stress (OS) in genesis of SVI and cardiovascular (CV) risks in salt-preferring prehypertensives. The subjects were divided into no-salt-preferring (NSP, n = 87) and salt-preferring (SP, n = 89) group based on their preference for salted food. Body mass index (BMI), blood pressure (BP) variability parameters including baroreflex sensitivity (BRS), heart rate variability (HRV) indices, autonomic function tests, IR, lipid risk factors, inflammatory and OS markers, and renin were measured in both the groups. Based on the contribution of various cardiometabolic risks to low-frequency–high-frequency (LF–HF) ratio of HRV, the marker of SVI was assessed by multiple-regression analysis. Prediction of prehypertension status by the LF–HF ratio was assessed by bivariate logistic regression. BMI, heart rate, BP parameters, cardiac output, total peripheral resistance, LF–HF ratio, IR, atherogenic index, inflammatory, and OS markers were significantly increased, and BRS was significantly decreased in the SP group compared with the NSP group. There was an independent association of IR, atherogenic index, markers of inflammation and OS, and BRS with the LF–HF ratio in SP subjects, and the LF–HF ratio had significant prediction of prehypertension status in these subjects. It was concluded that IR, low-grade inflammation, atherogenic lipid profile, and OS contribute to SVI in SP subjects. Decreased BRS (the marker of CV risk) is linked to SVI, and SVI predicts prehypertension status in SP subjects.